Electoral Uncertainty, Income Inequality and The Middle Class1. (10th July 2016) - Mitra, Anirban; Mitra, Shabana
Abstract : We investigate how electoral competition affects the income distribution in society. We utilise a standard probabilistic voting setup where parties compete at two stages. Our model delivers that greater electoral competition in a district results in equalisation of incomes therein. We check for these relationships using data from Indian national elections which are combined with consumption expenditure data rounds from the National Sample Survey Organization (1987–8 and 2004–5) to yield a district level panel. Our OLS, 2‐SLS and IIV analyses consistently inform that close elections lead to lower inequality and polarisation indicating a larger middle class.